Retraction: Traditional methods used by mothers living in different regions of turkey for increasing breast milk supply and weaning - Tural Büyük, Esra (Progress in Nutrition, 2020)
Background: It is a known fact that traditional practices mothers use in increasing breast milk supply and weaning differ in different parts of countries and even among communities sharing the same city. This study was conducted to find out the use of herbal tea and some foods to increase breast milk, the traditional methods used for weaning and the factors influencing these. Methods: This study is descriptive and cross-sectional. Three cities in Turkey with different levels of development in terms of geographical and socio economic regions were chosenThe data of the study were collected through a questionnaire form developed by the researchers. Results: It was found that the mothers who received breast milk increasing training the most were in eastern region, while mothers in western region fed their babies with formula since they thought their milk was not enough and this result was found to be statistically significant (p<0.05). In our study, it was found that 42.1% of the mothers resorted to some plants and foods to increase breast milk. When the mothers were asked about how they weaned their babies, it was found that 38.2% pasted things like hair and wool or put tomato paste on the breast, 26.9% applied bitter food on the nipple while 27.7% stated that the babies stopped breastfeeding spontaneously. It was found that mothers